2013
DOI: 10.1167/iovs.13-11615
|View full text |Cite
|
Sign up to set email alerts
|

JAK1, but NotJAK2andSTAT3, Confers Susceptibility to Vogt–Koyanagi–Harada (VKH) Syndrome in a Han Chinese Population

Abstract: PURPOSE. Janus kinase 1 (JAK1), JAK2, and signal transducer and activator of transcription 3 (STAT3) play an important role in Th1 and Th17 differentiation and gene polymorphisms of these factors have been demonstrated to be associated with certain autoimmune diseases. The present study was performed to assess the association between JAK1, JAK2, and STAT3 polymorphisms and Vogt-Koyanagi-Harada (VKH) syndrome in a Han Chinese population. METHODS.A case-control study was performed in 737 Chinese VKH syndrome pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Four SNPs (rs6718902, rs10199181, rs2066802, and rs1547550) in the STAT1 gene were observed to be associated with MS in Italy and IgA nephropathy (IgAN) in Korea [39, 40]. In addition, an association was found between SNPs (rs2780815, rs310241, rs3790532, rs310230, and rs310236) in JAK1 and Behçet disease (BD) as well as Vogt-Koyanagi-Harada (VKH) syndrome [41, 42], two other common uveitis entities in China. There has been no report of associations between JAK-STAT signaling pathway genes and AAU, and thus we performed this case-control study to detect whether the five candidate genes were associated with AAU in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four SNPs (rs6718902, rs10199181, rs2066802, and rs1547550) in the STAT1 gene were observed to be associated with MS in Italy and IgA nephropathy (IgAN) in Korea [39, 40]. In addition, an association was found between SNPs (rs2780815, rs310241, rs3790532, rs310230, and rs310236) in JAK1 and Behçet disease (BD) as well as Vogt-Koyanagi-Harada (VKH) syndrome [41, 42], two other common uveitis entities in China. There has been no report of associations between JAK-STAT signaling pathway genes and AAU, and thus we performed this case-control study to detect whether the five candidate genes were associated with AAU in a Chinese Han population.…”
Section: Discussionmentioning
confidence: 99%
“…We used HaploView 4.2 software to evaluate the linkage disequilibrium (LD) and minor allele frequency (MAF) of the SNPs. Five SNPs of JAK1 , rs2780815, rs3790532, rs310230, rs310236, and rs310241 [41, 42], were selected. Since the SNPs rs3790532, rs310230, rs310236, and rs310241 are in strong LD with each other ( r 2 > 0.8, Figure 1), we only used rs310241 in our study.…”
Section: Methodsmentioning
confidence: 99%
“…VKH likely results from the complex interplay of genetic and environmental factors. [120][121][122][123][124][125][126][127][128] There are several criteria required for diagnosis. 129 …”
Section: Ocular Manifestationsmentioning
confidence: 99%
“…A recent study suggested that three SNPs of the JAK1 gene including GG genotype of rs310230, GG genotype of rs310236, and TT genotype of rs310241 were found to occur in lower frequencies in VKH patients than control subjects [[150]]. However, no significant link between the three SNPs and clinical manifestations of VKH disease was identified, and currently, there is no published data on the functional role of these SNPs of JAK1 [[150]].…”
Section: Reviewmentioning
confidence: 99%